Perbuatan Penyidik Dalam Menghalangi Proses Peradilan Pidana (Obstruction Of Justice) - Khoirunnisa, Nabila; Dewi, Erna; Putri, Ria Wierma; Maroni, Maroni; Siswanto, Heri (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Investigators as law enforcement officers in carrying out their duties, namely law enforcement officers, guards, protectors, and public servants play an important role in the efforts of the state government to maintain order and public safety in good performance. Obstruction of justice is an action that can be interpreted as an act that tries to obstruct the legal process or 'criminal act of obstructing the legal process'. The purpose of this writing is to find out the legal arrangements regarding obstruction of justice in Indonesia and the elements that can be said that the actions of investigators that can be classified as criminal acts obstruct the legal process or obstruction of justice. The research method used in this article is normative juridical. The results of the study show that obstruction of justice is generally regulated in the Criminal Code, including; Article 221 paragraph (1), Article 231 and Article 233. Regarding the regulations, it is clearly spelled out in the provisions of the legislation clearly regarding obstruction of justice so that this cannot be separated from the philosophical foundation of the principle of legality in criminal law, no criminal act, no there is a crime without a previous criminal law. Regarding the elements that can be said that the investigator who committed an obstruction of justice, namely: 1) The action caused a delay in the legal process (2) The perpetrator knew his actions or was aware of his actions; (3) The perpetrator committed or attempted a deviant act with the aim of interfering with the legal process. So for investigators who meet these elements can be said to meet the elements of the crime of obstruction of justice and can be given sanctions according to the applicable laws and regulations.